Tourism village financial management model: the interpretive structural model (ISM) approach / Naelati Tubastuvi, Dwi Winarni and Rhis Ogie Dewandaru - Tubastuvi, Naelati; Winarni, Dwi; Ogie, Rhis (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study aimed to find the development of an appropriate financial governance model that can be implemented in tourist villages. Good financial governance is expected to strengthen the management of tourist villages in terms of welfare or economic benefits. This study focussed on a financial management model with detailed stages and analyzed the factors needed to successfully implement the established model. The research method used was a mixed method to capture a value or view represented by experts and practitioners of tourist villages, and the analytical tool used was the Interpretative Structural Modeling. The results showed that the financial management model in tourist villages involves stakeholders, and human resources and technology needs. There were five stages of the management process, namely, identifying financial transactions, preparing financial reports, making financial reports, auditing, and controlling processes. The five stages can be used for a measurable payroll system, profit sharing with investors, use for internal purposes and can be a transparency tool with stakeholders. In addition, there were ten factors needed to support the success of the tourism village management model. The practical implication is that tourism villages' financial management becomes orderly, transparent, and accountable.